Life-cycle assessment of lightweight textile membrane partition walls - Neiva, Sara Daniela Oliveira (2012)
This paper analyze the environmental, functional and economical performances of some conceptual lightweights textiles membranes partitions walls and to compare one of them with two technologies present in Portuguese market: i) the heavyweight conventional hollow brick partition wall; and ii) the lightweight reference plasterboard partition wall. Advantages of use textile/ fibrous/ membrane based materials in partition walls are focused and they may contribute for the development of new partition wall technologies. The comparative evaluation of these solutions is based on a standard Life-cycle Assessment method.